1988
DOI: 10.1029/ja093ia10p11507
|View full text |Cite
|
Sign up to set email alerts
|

Average ion moments in the plasma sheet boundary layer

Abstract: Using four months of tail data obtained by the three‐dimensional plasma instrument on board the AMPTE/IRM satellite in 1986, we have done a statistical survey on the behavior of ion moments and related plasma parameters in the plasma sheet boundary layer and the immediately adjacent outer central plasma sheet. The more than 40,000 spin averages of ion density, ion bulk velocity, ion temperature, ion temperature anisotropy and ion β were analyzed with respect to differences between their values in plasma sheet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(152 citation statements)
references
References 31 publications
8
142
1
1
Order By: Relevance
“…This is true for both CLRs and CGRs. [Baumjohann et al, 1988[Baumjohann et al, , 1989. Red and blue colors are used to indicate CLRs and CGRs, respectively, while light red and light blue are reserved for RAND-Ls and RAND-Gs.…”
Section: Ecr Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…This is true for both CLRs and CGRs. [Baumjohann et al, 1988[Baumjohann et al, , 1989. Red and blue colors are used to indicate CLRs and CGRs, respectively, while light red and light blue are reserved for RAND-Ls and RAND-Gs.…”
Section: Ecr Strengthmentioning
confidence: 99%
“…[43] According to Baumjohann et al [1988Baumjohann et al [ , 1989, the ion b approaches small values in the PSBL, of the order of b ] 0.1, while the central plasma sheet corresponds to higher values, b^0.1. From Figure 5, we clearly see that the ratio between the number of CLRs and the number of CGRs is considerably larger in the rightmost bin (high b bin) as compared to the leftmost bin (low b bin).…”
Section: Ecr Locationmentioning
confidence: 99%
“…Extensive statistical studies of the plasma within the near-Earth magnetosphere have previously revealed the behaviour of such parameters (e.g. Baumjohann et al, 1988;Newell and Meng, 1992;Borovsky et al, 1998;Wing and Newell, 1998;Měrka et al, 2002;Tysganenko and Mukai, 2003;Wing et al, 2005;Neagu et al, 2005;Denton et al, 2005Denton et al, , 2006Borovsky and Denton, 2006a, b;Lavraud et al, 2005Lavraud et al, , 2006Thomsen et al, 2007;Nagata et al, 2007;Åsnes et al, 2008) under a variety of conditions. The primary aim of the work outlined in the current paper is to reveal the averaged bulk parameters in the magnetosphere as a first step to a determination of how such parameters evolve during geomagnetic disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, observing a high speed-flow event does not necessarily mean there is a substorm in progress [9,10]. However, because most of the time the convection speed in the plasma sheet is relatively low [11,12], the general view is that high-speed flows play an important role in plasma convection and studies of high-speed flows have been closely tied to substorm research.…”
Section: High-speed Flows In Magnetic Convection and Substormsmentioning
confidence: 99%